Karakteristik Fisik Pakan Ikan Buatan dengan Substitusi Manure Ayam - Rizki Eka Puteri; Raudhatus Sa'adah; Selly Ratna Sari; fitria tsani farda; efano Iga Safitri (Clarias : Jurnal Perikanan Air Tawar, 2021)
Livestock waste including poultry manure can be used as an alternative feedstuff for fish feed. Manure is an alternative protein source to reduce the use of protein raw materials for feed which is very expensive.The objective of this study was to evaluate physical quality of pellet supplemented with manure poultry with different level (10% and 15%). A completely randomized with 3 treatments and 4 replicates was used. Parameters observed were the buoyance, water stability and pellet hardness. The result showed suplementation of manure poultry up to 15% had no significant effect to buoyance, water stability and pellet hardness. In conclusion, feed formulated with manure poultry did not negatively affected water stability and pellet hardness. Feed technology to increase the buoyancy is required.